2001
DOI: 10.2166/wst.2001.0336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals (Cu, Pb, and Ni) on the compositions of EPS in biofilms

Abstract: A series of batch adsorption tests to estimate the biofilm capacity for removal of the heavy metals (Cu, Pb, and Ni) in wastewater were carried out. The metal sorption results were fitted to the Freundlich isotherm model to compare their sorption capacity. The change of the composition of EPSs (extracellular polymeric substances) was simultaneously represented by the ratio of carbohydrate to protein (C/P) when the biofilm was exposed to the heavy metals. EPS composed of slime loosely bound to the cell and caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 8 publications
1
31
0
Order By: Relevance
“…Marine biofilms increase EPS production in response to several heavy metals, including copper (Fang et al, 2002), while EPS content of river biofilms substantially declines on exposure to Ni(II) (Lawrence et al, 2004). The carbohydrate/protein ratio is frequently altered by heavy metals, but the changes observed vary widely in different studies (Jang et al, 2001;Lawrence et al, 2004). Modifications in EPS composition of biofilms are attributed to the selective pressure of the heavy metals on the community, which favours bacterial populations producing an EPS having the characteristics that confer resistance to a particular metal ion (Lawrence et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Marine biofilms increase EPS production in response to several heavy metals, including copper (Fang et al, 2002), while EPS content of river biofilms substantially declines on exposure to Ni(II) (Lawrence et al, 2004). The carbohydrate/protein ratio is frequently altered by heavy metals, but the changes observed vary widely in different studies (Jang et al, 2001;Lawrence et al, 2004). Modifications in EPS composition of biofilms are attributed to the selective pressure of the heavy metals on the community, which favours bacterial populations producing an EPS having the characteristics that confer resistance to a particular metal ion (Lawrence et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The EPS encasing a biofi lm protect cells from heavy metal stress by binding the metal ions or by retarding their diffusion within the biofi lm. Metals (Fe, Au, La, Cu) bound to biofi lm of Pseudomonas aeruginosa PAO1 signifi cantly exceeded those bound by planktonically grown cells [77,79].…”
Section: Biofi Lm Eps and Metal Bindingmentioning
confidence: 96%
“…In addition, carbohydrate : protein (C/P) ratio also plays a signifi cant role in monitoring the state of biofi lm process to remove heavy metals in the wastewater. In batch experiments, binding of Cu(II), Pb(II) and Ni(II) occurred with lowering of C/P ratio of EPS when exposed to Cu and Pb ions [77]. Using a rotating-disk biofi lm reactor it was demonstrated that biofi lms were more resistant to Cu, Pb and Zn than the stationary-phase or logarithmically growing planktonic cells [78].…”
Section: Biofi Lm Eps and Metal Bindingmentioning
confidence: 99%
“…It can be related to various defense mechanisms either specific (for instance metal efflux or 348 decrease of metal uptake by modification of channel or carrier proteins used by the metal ions to 349 enter the cells (Harrison et al, 2007) or non-specific, for instance production of metal-binding 350 EPS (Mason and Jenkins, 1995;Jang et al, 2001) to a metal. The fact that exposure to Pb 351 induced tolerance to both Pb and Zn but not to Cu suggests that, in this case, the exposed 352 community probably developed defense mechanisms that are specific to Pb and Zn.…”
Section: Pb Exposure Concentrations (Left Graphs) 287mentioning
confidence: 99%